Kupferschiefer and Other Sediment-Hosted Deposits in Central Europe: Field Trip Review - Huyck, Holly (Geoscience Canada, 1986)
Summary The "Kupferschiefer and Other Sediment-Hosted Deposits in Central Europe" field trip(22 May-1 June 1986), which focussed uponthe stratiform copper shale (Kupferschiefer)deposits of West Germany and Poland, was amajor success. Trip leaders effectively com-municated the stratigraphy associated withthese deposits, the sulphide zonation, andthe controls of mineralization (particularly lo-cation with respect to hematitic alterationzones — "Rote Fàule" — and to paleo-topography). Replacement textures by ox-ides and copper sulphides and cross-cuttingrelationships of ore zones with respect tolithologies indicate diagenetic to epigeneticemplacement of ore. While many crucialquestions have been answered, severalremain.